PENGARUH KOMITMEN TERHADAP DISIPLIN DALAM BERORGANISASI IBU PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI KAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Susi Susanti Sitanggang; Daeng Ayub Natuna; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the problem in this study is how high the organizational commitment of the PKK mothers is, how high is the organizational discipline of the PKK mothers and how much influence is the commitment to discipline in the organization of the PKK mothers in Maredan Barat Village, Tualang District, Siak Regency. While the purpose of this study was to determine the level of organizational commitment of PKK mothers, to determine the level of maternal organizational discipline and to determine the effect of commitment to discipline in organizations of PKK mothers in Maredan Barat Village, Tualang District, Siak Regency. This research is a type of ex post facto research, a quantitative descriptive study of two variables to determine the effect between variables, before looking for the effect it is necessary to find a correlation first. The number of samples in this study were 47 people. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. This was done using Microsoft Excel and SPSS version 23 for Windows. Descriptive statistical analysis was carried out to present respondent profile data in the form of mean and standard deviation of the questionnaire results, based on the demographics of the respondents, variables, indicators and questionnaire items, then inferential statistical analysis was carried out to test the results of the previous questionnaire. the formulated hypothesis. The results obtained were the level of organizational commitment of PKK mothers and high organizational discipline among PKK mothers. Furthermore, there is a significant influence between Commitment (X) on discipline in organizing PKK mothers (Y) in Maredan Barat Village, Siak Regency, a large influence of 33.30%, because there are still 66.70% which is determined by other factors which are not part of this research. This influence is illustrated by each increase in one unit of commitment (X) followed by an increase in organizational discipline (Y) of 0.684 one unit. With the Pearson correlation value, the product moment between social interactions in the family and achievement motivation is 0.577 and sig (2- Tailed) is 0.00.Key Words: Commitment, Organizational Discipline, PKK Mother